Transaksi Pihak Berelasi: Kompensasi Manajemen Kunci, Kinerja Akuntansi, dan Multiple Large Shareholders - Gandy Wahyu Maulana Zulma; Fitri Chairunnisa; Azolla Degita Azis (Universitas Batanghari Jambi, 2020)
The aim of this study is to examine whether multiple large shareholders held by the company can affect the relation between accounting performance and executive compensation, using panel data of all publicly company in Indonesia (except financialand mining industries) with the research period 2017-2019. The result shows that the existence of 2nd largest shareholders that owns more than 10% stocks and also if the board has representation from 2nd largest shareholders in the company, it can reduce the positive effect of accounting performance to executive compensation. This research findings could be as an additional literature in financial accounting and corporate governance area, and also for practitioners in Indonesia that if a firm has good controlling function from multiple large shareholders, it can reduce the opportunistic discretion from executive management if the company has performance evaluation based on earnings.